POLITIK IDENTITAS DALAM KONTROVERSI ISU DI INDONESIA - Dinar Astuti; Andi Agustang; Idham Irwansyah Idrus (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Identity politics refers to a political strategy that prioritizes and puts forward the importance of a particular group's identity politics approach, such as ethnicity, religion, gender, culture, and inter-group, to influence public opinion and gain political support. The issue of controversy becomes increasingly complex with identity politics; many groups have different political views depending on their identity because personal thoughts and attitudes tend to be influenced by group identity. It can be a source of conflict in society. Identity becoming too crucial in politics will result in polarization and strengthen stereotypes and discrimination in society. The research method used in this research is observation, literature study, and literature study from social media and the internet. For this reason, we must find a balance between identity recognition and unity as a broader society in politics. Shows that identity politics can play an essential role in controversial issues to resolve conflicts and promote dialogue that is inclusive of all groups, and must still be balanced with recognition and unity for the larger society to avoid polarization that can undermine our national political stability.